Development of adaptable and adaptive interface tutorial package using behavioural approach / Roslan Sadjirin - Sadjirin, Roslan (2005)
This project focuses on providing the relevant interface and content to the various levels of users. The targeted users are student from BSc (hons.) Information Technology and Bsc (hons.) Data Communication and Networking, Faculty of Information Technology and Quantitative Sciences, UiTM Shah Alam. Fuzzy logic inference Mamdani-style is used as an approach to construct user model. This project construct user model based on user's level and preferences of contents and section. Users are being modeled into 3 levels which is beginner, intermediate, and expert. In order the tutorial package to adapt to the user level and preference content, three variables are required to make the inference engine of this tutorial package can infer user behaviour. Behaviour is considered as a combination of those variables. The variables are level of current content, user session time during working on the piece of tutorial package, and score of the user after taking a quizzes. But the variable has been added during development phases. The new variables that being added is number of user attempting to the tutorial and current pages of the content. All the five variables together are used to infer user's level and preference contents. The new variables that have been added do not changed in the rules that has been constructed during design phases. Designing user model and studying user behaviour is taken place whereby the effectiveness of these models is important in order to implement adaptable and adaptive interface of tutorial package. Result from the testing and experimental to the selected users is evaluated to see whether the output is accurate with the rules in inference engine. Suggestion and recommendation is also described to improve the adaptive strategy.